빅데이터 산업의 개인정보침해 행위에 대한 경쟁법의 적용가능성 - 오승한 (경쟁법연구, 2018)
Recently, Antitrust analysis of Big-data industries has been one of debated issues. Although the collection of user data by online service providers, such as an Internet search engine, a free e-mail service, SNS, has been enormous growth and criticized as the cause of privacy infringement, consumers have benefitted from free on-line services. Many scholars, however, have focused on the situation where consumers are forced to allow conglomerate Big-data Businesses to collect their private information widely because they do not have alternative choices to switch their service providers into others, which try to protect their privacy. For this reason, some opinions suggest that Big Data presents an antitrust issue, and antitrust agencies inspect whether anticompetitive effect is coming from Big Data collect businesses and the harm should be remedied under the antitrust laws. On the other hands, several commentators have opposed antitrust intervention in Big-data realm based on the argument that no entry barrier exists in the Big-data industry and anyone, who wants to collect the user data, could operate the same business as the current big-data service providers do. This article reviews the reality in big-data businesses and the implications of Big Data on competition. After considering non-price competition for free service, this essay will address the role of antitrust in Big Data issues.
Keywords: 빅데이터; 정보수집; 데이터 이동성; 프라이버시 보호; 사전 동의 원칙; Big-data; Privacy; Data Collection; Data Portability; Opt-in